A social–ecological study of stock structure and fleet dynamics in the Newfoundland herring fishery. (1st June 2017) - Paterson, Barbara; Neis, Barbara; Stephenson, Robert L; ,
Abstract: Successful management of small pelagic fisheries is critical in integrated ecosystem based approaches and requires understanding of how the ecological dynamics of pelagic stocks mesh with the economic and social dynamics of commercial fisheries and the larger systems within which they operate. Combining insights from stock assessments with those from local fishers, scientists, and managers, can help identify knowledge gaps that could jeopardize stock resilience. This article presents results from a social-ecological, mixed-methods study that combines insights from science and from interviews with fishermen, scientists, and managers of small pelagic fisheries in western Newfoundland, Canada (NAFO division 4R) and in NAFO division 4X. Different approaches to herring management are used in the two areas. In area 4R fishing for herring ( Clupea harengus ) is part of a complex multi-species, multi-gear fishery; most harvesters who target herring also target Atlantic mackerel ( Scomber scombrus ). Harvester interviews indicate herring in 4R, like herring in 4X and elsewhere, have substantial within-species stock structure, but that it is not well-documented in science and not well protected under the current management system. Further, fishing strategies in the competitive mackerel fishery in which the herring vessels are involved may contribute to the risk of over-fishing on some herring populations.